'Where Your Treasure’: A Consideration of Jesus’ Teaching on Possessions - Je'adayibe, Gwamma D. (African Journol of Evangelical Theology, 2001)
The Christian Church needs to develop a theology of riches, just as much as a theology of poverty. The contemporary world is marked by commercialism, the open market system and a consumer driven economy. Some elements of the Christian community have bought into this and have fallen into a distorted understanding of the biblical view of riches as they loudly proclaim a prosperity gospel. In this article Dr. Gwamna Je 'Adayibe provides us an important anecdote to materialism by examining our Lord's teaching on material possessions. This is a needed corrective to the prosperity gospel promulgated in various circles.
free